Mandibular overdenture retained by telescopic crowns and ball attachments on semierupted premolars - Elisa C Knebel; Paulo C A Maccari; Rosemary S A Shinkai (Wolters Kluwer Medknow Publications, 2022)
This clinical report describes the oral rehabilitation with a mandibular overdenture retained by telescopic crowns and ball attachments on semierupted permanent teeth with a 5-year follow-up. A female patient used an old complete denture in the maxilla and was willing to extract her remaining mandibular teeth to have new dentures. The treatment included preservation of semierupted premolars because of the high surgical risk for mandibular fracture and paresthesia, a new maxillary complete denture, and a mandibular overdenture supported by combined telescopic crowns and ball attachments. The prosthetic rehabilitation restored function and esthetics with high patient satisfaction after 5 years in function.